The Value of curiosity : the story of Christopher Columbus - Johnson, Spencer (La Jolla, CA : Value Comm., Inc Pub, 1977)
Demonstrates the value of curiosity in the life of Christopher Columbus.
Keywords: Columbus, Christopher; Explorers--Spain--Biography; Curiosity; Explorers